Resolution of Smell and Taste Dysfunction in COVID-19 Patients - Jutarat Chantaroje, M.D.; Nilnetre Mahathanaruk, M.D.; Phurich Praneetvatakul, M.D. (Thai Journal of Otolaryngology Head and Neck Surgery, 2023)
Abstract Introduction: Smell and taste dysfunction is one of the most common manifestations in COVID-19 patients. The symptom can be either temporary or persistent, with variation of severity, incidence and resolution rate in each study. Mechanism and factors that affect the recovery of symptom are still unclear. Therefore, this study aims to explore about these issues in order to provide treatment options and symptom prevention. Objectives: Primary objective of this study is to explore the resolution rate of smell and taste dysfunction in COVID-19 patients who were admitted in Ramathibodi hospital and affiliated hospitels during March – June, 2021. Secondary objectives are the duration and onset, along with the associated factors and effects of the symptom. Methods: This study was designed to be retrospective. The data was derived from medical records and inquired by phone to collect the patient’s basic information, comorbidities, history of COVID-19 vaccination before admission, treatment regimens, symptom of olfactory and gustatory dysfunction. The 12-item questionnaire, which was adapted from DyNaChron questionnaire, was also applied to this study. Results: There was 294 participants included in this study. Incidence of smell and taste dysfunction was 156 patients (53.1%) with median of onset of symptom at date of illness (DOI) 3. The resolution rate was 95.5% with median of duration at 7 days. 7 participants (4.5%) had permanent symptom. Medications was not associated with resolution rate, but patient groups who received favipiravir and systemic steroid were less affected by sticky and hazardous substance odors than those who did not receive the medications. Conclusion: Smell and taste dysfunction in COVID-19 patients is the symptom with high incidence, but also has high resolution rate. Some associated factors regarding cause and effect relationship are still inconclusive and need further investigation. Keywords: COVID-19, SARS-CoV-2 virus, smell dysfunction, taste dysfunction